Physical Exercise to Improve Immunity During the Pandemic Covid-19 - Yolinda Suciliyana; Widyatuti Widyatuti (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
Maintaining body immunity throughout the COVID-19 pandemic is one of the efforts to protect the body in opposition to disease. Adequate physical exercise is very necessary to prevent the body from attacking disease. This literature review objectives to determine the advantages of physical exercise to expand body immunity for the duration of the COVID-19 pandemic. This study uses a literature review. Literature searches were collected using online database such as Science Direct, Springer Link, Wiley online Library, SAGE publication, NCBI and Google Scholar so that 12 articles were used in this literature review that published from 2019-2021. These articles are then analyzed by narrative literature review. Studies exhibit that moderate physical exercise can enhance body immunity and respiratory function. Moderate types of physical exercise such as aerobics can increasing the immunity by using the increasing the degree and function of T-lymphocytes, immunoglobulins, mainly Ig A and Ig G, regulating C-reactive protein levels to prevent limit lung feature and extend the vital capacity of the lungs. Regular physical workout of moderate intensity has been proven to extensively affect the immune system and reduce the threat of infection disease.